Proceedings of the 23rd ACM Conference on Hypertext and Social Media 2012
DOI: 10.1145/2309996.2310012
|View full text |Cite
|
Sign up to set email alerts
|

Storyspace

Abstract: In a curated exhibition of a museum or art gallery, a selection of heritage objects and associated information is presented to a visitor for the purpose of telling a story about them. The same underlying story can be presented in a number of different ways. This paper describes techniques for creating multiple alternative narrative structures from a single underlying story, by selecting different organising principles for the events and plot structures of the story. These authorial decisions can produce differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The benefits of providing contextual information, both contextual and physical, [55], provides participants with the opportunity to engage in meaning-making as they engage with the DCI and the elements provided by SIT. In essence, participants were self-motivated, exploring the DCI on their own terms, discovering connections and forming relationships in accordance with the visitor-as-curator model encouraged both in analogue and digital museum experiences [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of providing contextual information, both contextual and physical, [55], provides participants with the opportunity to engage in meaning-making as they engage with the DCI and the elements provided by SIT. In essence, participants were self-motivated, exploring the DCI on their own terms, discovering connections and forming relationships in accordance with the visitor-as-curator model encouraged both in analogue and digital museum experiences [15].…”
Section: Discussionmentioning
confidence: 99%
“…DCIs also provide tools for building narratives, an avenue of research explored by many scholars studying digital cultural heritage. Much work has been undertaken to better understand the role of narrative in learning and meaning-making [9] [30] and has been applied to cultural heritage, with scholars exploring how connections between DCIs might support narrative, and therefore learning [55] [54] [35] [36], as well as the direct application of narrative, as a teaching aid [53] [33]. While our study did not intend to communicate a specific narrative, we observed that given the opportunity, visitors will provide their own narratives, as they engage in meaning-making.…”
Section: Introductionmentioning
confidence: 99%